The Comparing of Olsen and Joret-Hebert methods for extraction of available phosphorus in soil different in the content of calcium carbonate, and determination optimum shake time (Journal of Hama University, 2021)
This search was conducted during 2019 in order to compare Olsen,s method with Joret-Hebert,s method for extraction of available phosphorus in soil with increasing added calcium carbonate: blank(9% CaCO3), 15%, 20%, 25%, 30%, 35%. And the phosphorus was added to treatments and blank to reach into sufficient level (15 mgP/kg). Samples were incubated in the laboratory for two months, and the available phosphorus was determined by two methods after addition of calcium carbonate during the fallowing times: (one week, two weeks, one month, 1.5 month, 2months), and to determine available phosphorus with two methods by different shake times: (1/2 hour, 1 hour, 2 hours), and the determination of optimum shake time for extraction the highest quantity of available phosphorus and the effect of calcium carbonate on this quantity. The results showed: exceeding of olsen,s method in available phosphorus quantities in comparison with Joret-Hebert,s method, so the level of available phosphorus ranged between sufficient and medium for olsen, whereas  it was between medium and weak and very weak for Joret-Hebert.The shake time of one hour was the best  for olsen,s available phosphorus in comparison with 1/2 and 2 hours, whereas  the shake time of 2 hours was the best for Joret-Hebert in comparison with 1/2 and 1 hours, but it gave less phosphorus level than olsen,s method in all treatments.The increasing of percentage of calcium carbonate in soil caused decreasing in quantity of available phosphorus and extracted with both of methods, and after the first week of incubation time, the differences in quantity of available phosphorus between treatments  increasing added calcium carbonate appeared, but they were not significant, and after 1 month of incubation these  differences between blank(9% CaCO3) and 35% became  significant.